The Effect of Major, Education, and Skill Match on Job Satisfaction and Turnover Intention among Culinary Arts Graduates - Tae-Kyun Na; In-Young Jung; Saem Han (Tourism and Hospitality)
This study aims to investigate the impact of job match on turnover intention and job satisfaction within the culinary industry. To achieve this purpose, the study analyzes data from 264 graduates of culinary-related programs who participated in the Graduate Occupational Mobility Survey (GOMS). The findings revealed that the better the match between a graduate’s major and their job, the more significantly turnover intention decreases and job satisfaction increases. In contrast, skill and educational matches were found to have no statistically significant impact on these outcomes. Additionally, the primary reasons for turnover include low salaries, inadequate job match, and uncertainty about future opportunities within the organization. Therefore, to ensure that culinary graduates can smoothly transition into the culinary field after graduation, educational institutions and the industry must continuously develop HR systems and programs that reflect the values of these graduates.